2014
DOI: 10.1007/s11356-014-2961-1
|View full text |Cite
|
Sign up to set email alerts
|

United States National Sewage Sludge Repository at Arizona State University—a new resource and research tool for environmental scientists, engineers, and epidemiologists

Abstract: Processed municipal sewage sludges (MSS) are an abundant, unwanted by-product of wastewater treatment, increasingly applied to agriculture and forestry for inexpensive disposal and soil conditioning. Due to their high organic-carbon and lipid contents, MSS not only is rich in carbon and nutrients but also represents a ‘sink’ for recalcitrant, hydrophobic and potentially bioaccumulative compounds. Indeed, many organics sequestered and concentrated in MSS meet the U.S. Environmental Protection Agency's definitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 29 publications
(52 reference statements)
0
47
0
2
Order By: Relevance
“…Two samples were collected at ten POTWs, either because the facility had more than one treatment system and produced two types of final SS, or for quality assurance purposes, as well as one single grab sample at the remaining 64 facilities (Table S1). After the completion of TNSSS, the samples were acquired by the Halden Laboratory and archived at -20 o C as part of the Human Health Observatory (H2O) and National Sewage Sludge Repository (NSSR) at Arizona State University [36]. Eight samples were either missing or broken during shipment and handling.…”
Section: Standards and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two samples were collected at ten POTWs, either because the facility had more than one treatment system and produced two types of final SS, or for quality assurance purposes, as well as one single grab sample at the remaining 64 facilities (Table S1). After the completion of TNSSS, the samples were acquired by the Halden Laboratory and archived at -20 o C as part of the Human Health Observatory (H2O) and National Sewage Sludge Repository (NSSR) at Arizona State University [36]. Eight samples were either missing or broken during shipment and handling.…”
Section: Standards and Reagentsmentioning
confidence: 99%
“…In that study, SS samples were collected from 74 POTWs that employ secondary treatment or better in 2006/2007 [35]. Several pollutants have been analyzed 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 5 in these samples and the results have been published [29,[36][37][38][39]. However, no earlier study has reported the occurrence of bisphenols in SS from nationally representative samples.…”
Section: Introductionmentioning
confidence: 99%
“…EPA 2007, 2009; Venkatesan et al, 2014a). These representative samples were collected from more than 160 WWTPs across the contiguous United States.…”
Section: Methodsmentioning
confidence: 99%
“…The number of hazardous chemicals detected in MSS is considerable and constantly increasing (U.S. EPA, 2009; Venkatesan et al, 2014a, 2014b). Many of these contaminants are known endocrine disruptors, carcinogens and potent toxicants to aquatic organisms and humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation